Piam Sook School : the Community Management Modelfor an Aging Society in the 21st Century, Chiang Mai Province - Jeena, Yurathorn (Journal for Developing the Social and Community, 2018)
This paper demonstrates a management model of the elderly school. The school is a community organization which aims to prepare the aging society for the 21st century. This participatory action research is a case study at Piam Sook School, San Pong Sub-District Municipality, Mae Rim District, Chiang Mai Province. The target groups were administrators, staff of San Pong Sub-District Municipality, community leaders, staff at the Sub-District Hospital, Committees of Piam Sook School, and the elderly from San Pong Sub-District. The data was obtained and analyzed by a qualitative data analysis. The findings show that : (1) the activities held at Piam Sook School were developed based on the concepts of preparing the aging society. The aims of the activities were to encourage the elderly to live a fulfilling life and to be the teachers of wisdom for the community. The activities held emphasizedphysical, mental, economical, and social, under the concept of “Collaborative thinking, participating, and engaging for the elderly of Piam Sook School”; (2) the management model of Piam Sook School as the community organization for the 21st century was developed based on the integration of the elderly within the Sub-District, administrative organization of the school, participation for the civil society, types of activities or curriculum for the elderly people, budget, suitable places and the environment. This research suggests that the management model of Piam Sook School could be used as an example for other communities to set up the elderly school and prepare for the aging society in Thailand.